Pediatric stroke - deVeber, Gabrielle (Henry Stewart Talks, 2008)
Different causes for stroke and approaches to stroke treatment in infants, children and adults, Often multi-factorial role of anticoagulants, Different from atherosclerotic adult stroke, Need for multicentre collaboration to produce evidence on which to base treatment, Need for early and specific diagnosis and triage to centre with expertise
Archived at 2020/04/30